Simplify
(a)
e+ e + e
b)e+f+e+f+e
(c) 2a+3a
Răspunsuri la întrebare
Răspuns de
3
Răspuns:
Explicație pas cu pas:
a) e + e + e = e·( 1 + 1 + 1) = 3e
b) e + f + e +f + e = e·( 1 + 1 + 1) + f·(1+1) = 3e + 2f
c) 2a + 3a = a·(2+3) = 5a
Răspuns de
2
Răspuns:
A) e+e+e=e×(1+1+1)=e×3=3e
B)e+f+e+f+e=e×(1+1+1)+f×(1+1)=3e+2f
C)2a+3a=5a
Explicație pas cu pas:
Corect...
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Engleza,
9 ani în urmă
Biologie,
9 ani în urmă